Utilization of Vegetable and Fruit By-products as Functional Ingredient and Food - Lau, Ke Qi; Sabran, Mohd Redzwan; Shafie, Siti Raihanah (Frontiers in Nutrition, 2021)
With the constant growth of human population, the global demand for food is increasing annually. Food security is an arising issue due to decreased resources and massive waste production from the agricultural sector. For example, not all parts of fruits and vegetables are consumed by consumers, and this phenomenon can lead to huge amounts of food wastes are produced globally. Besides, non-utilized agriculture by-products including seed coat, hull, husk, peels, seeds and pomace can cause environmental issues. Hence, efficiently utilizing food waste such as vegetable and fruit by-products could be a way to increase food sustainability, and in line the United Nation Sustainable Development Goal (SDG) to ensure sustainable consumption and production patterns. Moreover, certain agriculture by-products are reported to have high nutritional value and could be potentially used as functional ingredient and food in the food industry. This review article summarizes findings on the development of new functional foods by utilizing different types of agriculture by-products, i.e vegetable and fruit by-products as ingredients. Besides, the nutritional values, processing methods, product acceptability and potential uses of these vegetables and fruits by-products are also discussed. These by-products can be alternative source of nutrients to support the global demand of functional foods and as one of the strategies to cope with food insecurity. Studies have shown that different types of agricultural waste were well incorporated in the development of functional food such as bakery products and dairy products. Of great importance, this review article provides an insight of the nutritional value, health benefits and utilization of agricultural waste.